Plasma Protein Layer Concealment Protects Streptococcus pyogenes From Innate Immune Attack - Jagau, Hilger; Packirisamy, Swathi; Brandon, Kyle; Herwald, Heiko (Frontiers in Cellular and Infection Microbiology, 2021)
Early recognition and elimination of invading pathogens by the innate immune system, is one of the most efficient host defense mechanisms preventing the induction of systemic complications from infection. To this end the host can mobilize endogenous antimicrobials capable of killing the intruder by perforating the microbial cell wall. Here, we show that Streptococcus pyogenes can shield its outer surface with a layer of plasma proteins. This mechanism protects the bacteria from an otherwise lytic attack by LL-37 and extracellular histones, allowing the bacteria to adjust their gene regulation to an otherwise hostile environment.